Simultaneous measurement of thirteen steroid hormones in women with polycystic ovary syndrome and control women using liquid chromatography-tandem mass spectrometry. - Candace C Keefe; Mildred M Goldman; Ke Zhang; Nigel Clarke; Richard E Reitz; Corrine K Welt (PLoS ONE)
Background The measurement of adrenal and ovarian androgens in women with PCOS has been difficult based on poor specificity and sensitivity of assays in the female range. Methods Women with PCOS (NIH criteria; n = 52) and control subjects with 25-35 day menstrual cycles, no evidence of hyperandrogenism and matched for BMI (n = 42) underwent morning blood sampling. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) was used to simultaneously measure 13 steroids from a single blood sample to measure adrenal and ovarian steroids. Androgen and progesterone results were compared in the same samples using RIA. Results Testosterone, androstenedione, progesterone and 17OH progesterone levels were higher when measured using RIA compared to LC-MS/MS, although the testosterone RIA demonstrated the best agreement with the LC-MS/MS using a Bland-Altman analysis. Results using LC-MS/MS demonstrated that the concentration of androgens and their precursors were higher in women with PCOS than controls [median (2.5, 97.5th %ile); 1607 (638, 3085) vs. 1143 (511, 4784) ng/dL; p = 0.03]. Women with PCOS had higher testosterone [49 (16, 125) vs. 24 (10, 59) ng/dL], androstenedione [203 (98, 476) vs. 106 (69, 223) ng/dL] and 17OH progesterone levels [80 (17, 176) vs. 44 (17, 142) ng/dL] compared to controls (all P<0.02), but no differences in serum concentrations of the adrenal steroids DHEAS, cortisol, corticosterone and their 11 deoxy precursors. Women with PCOS also had an increase in the product:precursor ratio for 3β-hydroxysteroid dehydrogenase [22% (6, 92) vs. 20% (4, 43); p = 0.009]. Conclusion LC-MS/MS was superior to RIA in measuring androstenedione, progesterone and 17OH progesterone levels, while testosterone measurements were better matched in the two assays. Androgen levels were higher in women with PCOS in the absence of a difference in adrenal-predominant steroids. These data support previous findings that the ovary is an important source for the androgen excess in women with PCOS.